BIOINFORMATICS — INSTRUMENT INTERPRETATION PROTEOMIC PROFILES OF MEAT PROTEIN - N. L. Vostrikova; I. M. Chernukha (Теория и практика переработки мяса, 2017)
Proteomic technologies have proven very eﬀective for detection in meat products of biochemical changes, such as changes in heat resistant and species-speciﬁc proteins that could be relevant bio-markers.In the work presented in this report (for the period of 2013–2016), several tissue-speciﬁc proteins were detected in the samples of meat and specially developed meat products using proteomic technologies and identiﬁed as individual biomarkers in meat product control.The existence of a large number of diﬀerent proteins resulted in the need to create information arrays — databases (or banks). Currently, there are a number of general and specialized databases that are available online to anyone interested. When studying protein proteomic proﬁles, many scientists stop at the stage of two-dimensional electrophoregrams sometimes even without ideas about the future prospects of using modern instruments and bioinformation resources to conﬁrm or refute their hypotheses, and sometimes just to identify. This overview shows the chain of actions that allows going from proﬁling proteins in the gel to a speciﬁc interpretation of the results. Studies in this ﬁeld have enabled formulating and signiﬁcantly expanding the approaches to the identiﬁcation and quantiﬁcation of protein markers of quality, functionality and safety of meat raw material (detection of falsiﬁcation) in the ﬁnished meat products. Based on the obtained data, the information was systematized using bioinformatics techniques with creation of the unique Atlas «Proteomic proﬁles of farm animal meat proteins.»